Comparative phenology and growth in different species of the Mediterranean maquis of central Italy - Lillis, M; Fontanella, A (Plant Ecology, 1992)
A phenomorphological survey was carried out in central Italy to study the effects of increasing water stress on some characteristic species of the Mediterranean maquis. Nutrient content and leaf water potential were examined. The results show that three different groups exist which diverge in the mod- ulation of growth activity. 1) Evergreen sclerophyllous species (e.g. Pistacia lentiscus, Phillyrea media, Arbutus unedo, Ruscus aculeatus), which were supposed to be drought-tolerant, in fact limited their growth activity to a brief period before aridity increased. A similar growth pattern was exhibited by those spe- cies (e.g. Quercus ilex, Erica arborea, Smi/ax aspera) that stopped producing new leaves and branches during the driest season and that recovered after the first rain; i.e., their growth period lasted longer. 2) Drought-deciduous species (e.g. Calicotonw villosa) that adopted the drought-avoidance strategy had two vegetative periods interrupted by a phase during which they completely shed their leaves. 3) Semi- deciduous species (Cistus monspeliensis) with mesophitic leaves adopted an intermediate response. These grew even in the dry and cold season.
Keywords: mediterranean species; nutrient use; phenomorphology; water use

Productivity and nutrient uptake in a holm oak (Quercus ilex L.) stand and during regeneration after clearcut - Rapp, M; Derfoufi, F; Blanchard, A (Plant Ecology, 1992)
The effect of clearcutting on biomass production and nutrient consumption was examined during the two years in a clearcut and a mature Quercus ilex L. coppice. The comparison was limited to the leaf com- partment and to the annual shoots, which were the only con]parable compartments in the two situations. At the same time, the dynamics of the nutrient pool (N, P, K, Ca, Mg), monthly uptake and recycling from the foliage, were studied. The second year after cutting, the leaf production was roughly the same at the two sites. However, the photosynthates appear to be used differently: in the young stand the perennial wood production was greater than in the mature stand, where the maintenance costs are higher. This is corroborated by the patterns of nutrient use.
Keywords: biomass; Clearcut; coppice; nutrient use; production; Quercus ilex L.